Mixed Method Research In Practice Healthy Reproduction Of Young Women In The Remote Indigenous Community Of The Suku Anak Dalam (SAD) Along The Trans-Sumatra Highway In Jambi Province - Asparian, Asparian; Azhary, Muhammad Rifqi; Siregar, Sri Astuti; Lanita, Usi (LPPM Universitas PGRI Sumatera Barat, 2023)
The research